E-logistics formation factors - Δημήτρη Φωλίνα (SPOUDAI Journal of Economics and Business, 2005)
In this paper Supply Chain, E-Business and Virtual Enterprises approaches / research areas interdependency is examined in order to define the new operation framework for Logistics Management. The paper argues that the focus of Logistics Management has shifted from engineering efficient functional processes to the coordination of activities in virtual web-based networks. This transformation is the outcome of the evolution process of Information and Communication Technologies and especially Internet. It is clear today that as organizations enter a new age of global competitiveness, electronic (e-) Logistics Management would serve as a tremendous catalyst for this new age and aid them in their quest for market share and profitability. JEL Classification: L23, M11